LAMINOPLASTY AND CORPECTOMY IN THE TREATMENT OF CERVICAL SPONDYLOTIC MYELOPATHY - Dmitrievich,Dreval’ Maxim (2018)
ABSTRACT Introduction: Cervical Spondylotic myelopathy (CSM) is a disabling manifestation of extended cervical stenosis characterized by pronounced neurological dysfunction. Decompressive interventions contribute to significant regression of symptoms and, in some cases, complete recovery can be achieved. Objective: To explore the potential of laminoplasty in patients with extended cervical spondylotic stenoses complicated by myelopathy, and to develop approaches for surgical intervention in these patients. Methods: Fifty-six patients were included in the study. Laminoplasty was performed in 34 patients. Corpectomy was performed in 22 patients who made up the comparison group. The frequency and initial severity of concomitant non-neurological disorders in both groups were comparable. Results: Indications for laminoplasty were determined. They include: symptoms of spondylotic myelopathy, three or more levels of compression, preservation of lordosis, absence of signs of segmental instability, inability to perform anterior decompression, and age over 55 years. The presence of signs of segmental instability, kyphotic deformation, and history of mental disorders may be considered as contraindications for this surgery. Conclusions: Due to a number of advantages, laminoplasty is the treatment of choice for extended cervical spondylotic stenosis. Adequate selection of patients based on the evaluation of clinical symptoms, extension of stenosis, neurological signs and neuroimaging features enable excellent results to be achieved. Level of Evidence: II. Type of Study: Prospective comparative study.